Silica Sulfuric Acid as an Efficient Reagent for Bamberger Rearrangement of Phenyl Hydroxylamine Derivatives in Solvent-Free Conditions - BADRI, RASHID; REZA SHUSHIZADEH, MOHAMMAD (Asian Journal of Chemistry, 2010)
Phenyl hydroxylamines undergo Bamberger rearrangement in the presence of silica sulfuric acid under solvent-free conditions to afford the corresponding 4-amino phenol derivatives in high yields.